Bakson's pioneering the beginning of a new era in homoeopathy (Homoeopathy for All, 2022)
Homoeopathy is a 200-year-old form of alternativemedicine that stimulates a healing response andstrengthens the body's ability to heal itself. Manystudents now choose to pursue degree course tobecome homoeopathic doctors.In the past, a candidate was required to pass the 10+ 2or other equivalent exam with 50% marks, after 12years of study with the last 2 years of studycomprising Physics, Chemistry and Biology tosecure admission in BHMS course. Now, admissionsto BHMS/MD Courses are done on the basis ofNational Eligibility cum Entrance Test that isconducted by the Central Board of SecondaryEducation(CBSE).
Keywords: Education; equivalent; Central Board of Secondary Education(CBSE).